The Effect of Organizational Justice on Intention to Leave with Job Satisfaction as a Mediation Variable (Study at PT. BCA Finance Surabaya) - Muhammad Alfathan Yusanura Putra; Tina Melinda (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study examines the direct and indirect effects of organizational justice on intention to leave. However, on the mediating variable, this study used job satisfaction. This quantitative research distributed questionnaires to 52 PT. BCA Finance Surabaya marketing staff. The research found that organizational justice has a positive and significan effect on job satisfaction, job satisfaction has a significant negative effect on intention to leave, and organizational justice has a significant negative effect on intention to leave and it is concluded that job satisfaction plays role as mediation part in the relationship between organizational justice against intention to leave. Organizational justice positively influenced intention to leave from marketing staff at PT. BCA Finance Surabaya and used job satisfaction as mediation variable. Further, this study is among the many that applied the organizational justice and job satisfaction concepts to the banking sector. The implication for management is to improve product quality through standard improvement, product development, and innovation. In addition, on, improving service quality through training and development programs for employees, improving SOPs, and physical facilities. The goal is to increase employee’s satisfaction and affect the level of repurchase intention. This research’s limitations include the study only uses one independent variable, namely organizational justice to explore and find useful information about the reasons for employees to leave their jobs, in this case the marketing employees of BCA Finance Surabaya. Thus, it is possible that there are other variables outside the study that also affect employee satisfaction and which ultimately affect the reasons for employees to leave work.